A NEW HISTORICIST READING OF WOLE SOYINKA’S THE STRONG BREED AND FEMI OSOFISAN’S NO MORE THE WASTED BREED (Isagoge - Journal of Humanities and Social Sciences, 2022)
Scapegoatism as a metaphor for selfless or altruistic leadership and patriotism is a prominent motif in Wole Soyinka's dramatic oeuvre. Based on ritualisation of theatre through martyrdom syndrome adapted from the mystic cultural worldview of the Yoruba, human sacrifice is emphasised as a transformational apparatus for cleansing and for social redemption in his plays. Besides Death and the King's Horseman, his The Strong Breed is premised on human sacrifice as a means for averting social disruption or communal tragedy. However, critics and scholars have advanced that Femi Osofisan's No More the Wasted Breed parodies Soyinka's The Strong Breed on the basis of the needlessness to waste an icon before restoration of order and peace in society materialises. Against this backdrop, this paper attempted a comparative study of the two texts deploying the new historicist literary theory for analysis with concentration on the popular scholarly opinion of the latter text's critique on the former play. The researchers found out that the latter (Osofisan's No More the Wasted Breed) is still an atavistic echo of the former (the text it criticises) because it is not an outright condemnation of human sacrifice, it only succeeds in questioning the class from which the prey is chosen. The paper then concluded that the so-called superior argument or antithesis of No More the Wasted Breed is not impeccable as regards the logical formula for social re-ordering and regeneration.
Keywords: Historicism, Sacrifice, communal, reordering, society